"Badu" Tradition as Local Conservation and Food Sharing System for the Poor - Dasion, Agustinus Raja; Nugroho, Heru (KOMUNITAS: International Journal of Indonesian Society and Culture, 2020)
The purpose of this research is to describe the badu tradition as an effort to preserve local natural resources reasonably and becomes a system of equitable distribution of natural resources for the poor. This research uses ethnographic methods by identifying the structure of indigenous peoples that allows the application of the badu tradition from generation to generation. The results show two important things. First, the badu tradition is a traditional ecological knowledge of Watodiri, which contains rules and prohibitions in maintaining the balance of the marine ecosystem locally. This tradition supported by the belief that the sea has a spirit that needs to be maintained so that the sea can provide a life for the community. Second, the badu tradition shows the altruism of the Watodiri people through sharing the catch of those in need, such as widows and orphans. Badu is a food sharing system for the poor. Widows and orphans get a place and share in the celebration of the badu tradition. Widows and orphans have a special place in the social structure of Watodiri, so that; their lives are the responsibility of all Watodiri people.